Comprehensive Identification and Ranking of Factors Affecting the Credibility of Financial Reports in Iran in the Light of Stakeholder Theory and Organizational Legitimacy Theory - Ali Mostafaei; Aliakbar Nonahal Nahr; Fazel Mohammadi Nodeh (Iranian Journal of Accounting, Auditing & Finance)
Financial reports are essential for illustrating social realities and providing a solid informational foundation to meet the demands of financial markets and assess market economic performance. However, financial reports do not fulfill their intended role due to quality, stability, and dynamics issues, and existing literature has yet to offer a suitable framework to address these issues. This study introduces a new concept aimed at enhancing the credibility of financial reports, both now and in the future. Adopting a comprehensive approach, we identify and rank the factors that influence the explanation and realization of this concept. The theoretical framework supporting this new concept includes stakeholder and organizational legitimacy theories. The research methodology comprises two parts: the first involves theme analysis based on interviews with 18 experts, and the second uses the fuzzy Delphi method to analyze and rank components through a questionnaire administered to 60 participants. The four expert groups involved in the study were accounting information providers, accounting information users, independent and internal auditors, and financial and accounting researchers, all carefully selected via snowball sampling for their expertise and insights. The research was conducted in the latter half of 2022. Findings reveal that the factors affecting the credibility of financial reports, ranked by their influence, include profit quality, audit report content, stock status, market performance, the quality of the accounting information system, organizational culture, specific non-financial company characteristics, financial ratios, corporate governance, audit quality, mandatory and optional disclosures, and risk analysis.